Angiogenesis in Chronic Inflammatory Skin Disorders - Hyun Ji Lee (MDPI AG, 2021)
Angiogenesis, the growth of new blood vessels from preexisting vessels, is associated with inflammation in various pathological conditions. Well-known angiogenetic factors include vascular endothelial growth factor (VEGF), angiopoietins, platelet-derived growth factor, transforming growth factor-β, and basic fibroblast growth factor. Yes-associated protein 1 (YAP) and transcriptional co-activator with PDZ-binding motif (TAZ) have recently been added to an important angiogenic factor. Accumulating evidence indicates associations between angiogenesis and chronic inflammatory skin diseases. Angiogenesis is deeply involved in the pathogenesis of psoriasis. VEGF, angiopoietins, tumor necrosis factor-a, interleukin-8, and interleukin-17 are unregulated in psoriasis and induce angiogenesis. Angiogenesis may be involved in the pathogenesis of atopic dermatitis, and in particular, mast cells are a major source of VEGF expression. Angiogenesis is an essential process in rosacea, which is induced by LL-37 from a signal cascade by microorganisms, VEGF, and MMP-3 from mast cells. In addition, angiogenesis by increased VEGF has been reported in chronic urticaria and hidradenitis suppurativa. The finding that VEGF is expressed in inflammatory skin lesions indicates that inhibition of angiogenesis is a useful strategy for treatment of chronic, inflammatory skin disorders.